Ultrasound-assisted synthesis of substituted triazines and their corrosion inhibition behavior on N80 steel/acid interface - Salman M.; Ansari K.R.; Haque J.; Srivastava V.; Quraishi M.A.; Mazumder M.A.J. (My University, 2025)
The three substituted triazines were synthesized by ultrasound irradiation method and characterized by FTIR, 13C NMR, and 1H NMR. The corrosion inhibition behavior of the synthesized inhibitors on N80 steel in 15% HCl was studied using electrochemical analyses and weight loss methods. All three inhibitors exhibited excellent corrosion inhibition performance, and the best inhibition effect was shown by TZ-3 (93.2% at 800 mg/L). EIS measurements suggest that the corrosion inhibition process is a charge transfer controlled. The PDP results indicated that all the triazines are mixed-type inhibitors. Langmuir adsorption model is the best fit among the other tested isotherms. These molecules can act as promising acidizing corrosion inhibitors for the oil gas industry. FTIR, AFM, and UV-vis studies corroborate the adsorption of inhibitor molecules over the metal surface. © 2020 Wiley Periodicals, Inc.